Banks Performance and Impact of Market Orientation Strategy: Do Employee Satisfaction and Customer Loyalty Augment this Relationship? - Abuzid, Hamada Fawzy Thabet; Abbas, Muzaffar (International Review of Management and Marketing, 2017)
Banking sector performance directly reflects the manifestation of a government vision to facilitate in infrastructure support to economic performance of a country. How efficient a banking sector is and how good the sector takes care of customers, it triggers the economic growth. This research is an effort to measure the impact of market orientation strategy adopted by Saudi Arabia banks on their business performance under the influence of mediating variable such as employee and customer satisfaction. A number of banks listed on the Saudi financial market in Saudi Arabia were included in this research and a randomly selected sample consisted of banks managers, banks employees and the bank’s customers participated in the study. 66 managers, 253 employees and 288 customers were contacted and a total of 51 managers, 201 employees and 265 customers responded accurately to form part of the research. Thereby, the response rate was 77%, 79.4% and 92% respectively. Various SPSS and Amos tools were applied to perform statistical analysis of the model and variables. Considering the results of the data, the researchers are able to draw a conclusion which is also consistent with the past similar researches that market orientation strategy has a direct and positive influence on the banks financial, operational and functional outcomes provided that employee and customer satisfaction are properly taken care of. The findings also confirmed the positive mediating role of both variables i.e. employee and customer satisfaction in this relationship. Keywords: Performance, Satisfaction, Market Orientation, Saudi Arabia JEL Classifications: G2, L1